A Novel Electrochemical Sensor Based on Silsesquioxane/Nickel (II) Phthalocyanine for the Determination of Sulfanilamide in Clinical and Drug Samples. Issue 5 (6th February 2019) - Vanoni, Caio Raphael; Winiarski, João Paulo; Nagurniak, Glaucio Régis; Magosso, Hérica Aparecida; Jost, Cristiane Luisa
Abstract: This paper describes the immobilization of nickel (II) phthalocyanine‐tetrasulfonic acid tetrasodium salt (NiTsPc) in 3‐ n‐ propyl(3‐methylpyridinium) silsesquioxane chloride (Si3Pic + Cl − ). This hybrid material was synthetized and characterized by 29 Si NMR CP‐MAS, FTIR and DRS. The modified material, designated as Si3Pic + Cl − /NiTsPc, was used to build carbon paste electrodes to determine sulfanilamide (SFL) by differential pulse voltammetry. The modified electrode showed a higher current response when compared to the bare carbon paste electrode. The evaluation of SFL was possible in the presence of salicylic acid, commonly used in solid ointment compositions in a high concentration. Theoretical calculations using density functional theory were done aiming to shed light at dimerization process at SFL. The oxidation peak increased with increasing concentrations of SFL in the range of 35–301 μmol L −1 . The LOD and LOQ values obtained were 12 and 35 μmol L −1 of SFL, respectively. The novel electrochemical sensor was successfully applied for the determination of SFL in pet drug samples, urine and serum through the standard addition method. Validation was performed through a comparison with values obtained by the molecular absorption spectrometry method and there were no significant differences in the results, as confirmed by the statistical paired t ‐test. This demonstrates the promise of a new approach for analytical application in clinical and drug samples of sulfonamide compounds. Abstract :